J Fitopatol Indones 2017
DOI: 10.14692/jfi.13.2.35
|View full text |Cite
|
Sign up to set email alerts
|

Kepekaan Erythricium salmonicolor Penyebab Penyakit Jamur Upas pada Kemiri Sunan terhadap Suhu, Cahaya, dan Fungisida

Abstract: ABSTRAKGejala khas penyakit jamur upas ditemukan pada tanaman kemiri sunan (Reutealis trisperma) di Bogor. Penelitian ini bertujuan menentukan cendawan penyebab dan kepekaannya terhadap suhu, cahaya, dan fungisida. Cendawan diidentifikasi berdasarkan karakter morfologi. Inokulum diperoleh dari isolasi jaringan kulit batang terinfeksi. Uji patogenisitas dilakukan dengan menempelkan potongan cabang kemiri sunan yang sudah terkolonisasi pada bibit kemiri sunan dan diinkubasi di rumah kaca. Pengaruh suhu terhadap … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 7 publications
0
3
0
1
Order By: Relevance
“…Results showed that the symptoms of pink disease in A. crassicarpa were similar to the symptoms of pink disease in sunan hazelnut plants (Florina et al, 2017;Old et al, 2003). Some of the specific symtomatic stages of this disease were the cobweb stage, characterized by the appearance of thin white, shiny and silky mycelium that then sporadically developed and expanded ( Figure 3A & B).…”
Section: Resultsmentioning
confidence: 66%
See 1 more Smart Citation
“…Results showed that the symptoms of pink disease in A. crassicarpa were similar to the symptoms of pink disease in sunan hazelnut plants (Florina et al, 2017;Old et al, 2003). Some of the specific symtomatic stages of this disease were the cobweb stage, characterized by the appearance of thin white, shiny and silky mycelium that then sporadically developed and expanded ( Figure 3A & B).…”
Section: Resultsmentioning
confidence: 66%
“…Colonies growing on PDA for five days were white with clear concentric circles ( Figure 4E). Conidia were also found on rubber rods (Florina et al, 2017). However, conidia or sporulation structures were not observed on the colonies growing on PDA (Kwarteng et al, 2018;Akrofi et al, 2015).…”
Section: Scoresmentioning
confidence: 99%
“…Five levels of concentrations were tested ranging from 0 to 500 ppm. A piece of the fungal colony was planted onto a PDA medium that had been adjusted with each tested fungicides [14]. Each treatment used 4 petri plates as a repetition.…”
Section: Fungicide Sensitivitymentioning
confidence: 99%
“…Inokulasi dilakukan dengan memodifikasi metode Florina et al (2017). Inokulum berupa potongan batang tanaman yang terkolonisasi diganti dengan inokulum berupa potongan koloni patogen sebesar 7 mm ditempelkan pada batang utama bibit kopi umur 1 tahun yang dilukai dengan 3 tusukan per tempat.…”
Section: Pendahuluanunclassified